A73 DIETARY FIBRE IMPROVES INTESTINAL EPITHELIAL BARRIER FUNCTION THROUGH TLR4 ACTIVATION. (15th March 2019) - Baggio, C H; Shang, J; Nascimento, A M; Cipriani, T R; Stephens, M; von der Weid, P; MacNaughton, W
Abstract: Background: The beneficial effects of dietary fibre have been recognized for many years. These complex polysaccharides are indigestible and fermented by gut microbiota, promoting advantageous effects to intestinal mucosa indirectly. Polysaccharides also have direct effects on intestinal epithelial barrier function and we have previous shown that rhamnogalacturonan (RGal), a polysaccharide isolated from the plant Acmella oleracea, promotes barrier function in human colonic epithelial Caco-2 cells. However, the underlying mechanism of action of RGal remains unclear. Aims: We aimed to investigate if RGal directly enhances intestinal epithelial barrier function through TLR4 activation. Methods: Human TLR4/CD14/MD2 transfected HEK 293 reporter cells were incubated with RGal (1000 μg/ml) with/without C34 (TLR4 inhibitor, 10 ng/ml) for 24 hrs. Supernatants were collected and activation of TLR4 was detected by using the secreted alkaline phosphatase assay (Invivogen). LPS (10 ng/ml) was used as positive control. Caco-2 cells were seeded on Millicell supports for 6 days and treated apically with vehicle (0.01% DMSO in PBS) and C34 (100 ng/ml). After 1 hr, cells were mounted in Ussing chambers and treated apically with RGal (1000 μg/ml). Transepithelial electrical resistance (TER) and FITC-dextran flux were measured. In another set of experiments, the monolayers were treated apically with GF109203X (pan-PKC inhibitor, 500 nM), myristoylated PKCζ pseudosubstrate inhibitor (10 μM) and Go6976 (PKCα/β inhibitor, 10 nM) for 10 minutes before apical addition of RGal (1000 μg/ml). Results: Incubation of TLR4-expressing HEK cells with RGal (1000 μg/ml) activated TLR4 at similar levels compared with LPS (10 ng/ml). In addition, C34 (10 ng/ml) significantly inhibited both RGal and LPS activation without altering cell viability (assessed via MTT assay). Apical treatment of cells with RGal increased TER and reduced FITC-dextran flux compared to control. C34 reversed the RGal effects in TER. The RGal-mediated decrease in macromolecular permeability was dependent on PKC but not on PKCζ or PKCα/β. Conclusions: These data suggest that RGal enhances intestinal epithelial barrier function through activation of TLR4 and the PKC signaling pathway. Elucidation of RGal mechanisms of action could lead to new approaches to the treatment of inflammatory bowel diseases. Funding Agencies: NSERC